Altered hormonal patterns in borderline personality disorder mother-child interactions - Bonfig, Julia; Herpertz, Sabine; Schneider, Isabella (Psychoneuroendocrinology, 2022)
Background - Oxytocin, cortisol, and testosterone are involved in the processing of reward and stress and greatly influence mother-child interactions. Altered hormonal systems have been associated with borderline personality disorder (BPD), a disorder characterized by interpersonal deficits. Mothers with BPD tend to perceive interactions with the child as less rewarding and more stressful and interactions are often less reciprocal and have more negative states (i.e. constricted, tense, uncoordinated behaviors). Their children are at elevated risk for psychopathologies. Here, we studied underlying hormonal mechanisms of disrupted mother-child interaction in BPD. - Methods - Twenty-five mothers with BPD and 29 healthy mothers with their 18- to 36-month-old toddlers participated in a free-play mother-child interaction, which was evaluated with the Coding Interactive Behavior (CIB) Manual. Maternal blood samples were analyzed at baseline for oxytocin, cortisol, and testosterone, and after interaction for oxytocin and cortisol. - Results - Oxytocin decreased and cortisol remained unchanged in mothers with BPD while healthy mothers showed stable oxytocin and decreased cortisol after interaction. Testosterone basal levels were significantly higher in mothers with BPD. Cortisol reactivity and testosterone levels mediated the association between maternal BPD and dyadic negative states during interaction. - Conclusions - These findings suggest that alterations in oxytocin, cortisol, and testosterone contribute to disruptions in mother-child interaction in BPD. Interacting with their child might not result in reward and relief of stress in mothers with BPD in the same way as in healthy mothers. Further research is needed to understand more about dyadic bio-behavioral processes in order to provide targeted parenting support. This could break the cycle of transgenerational transmission and improve maternal and child well-being.